Study of the Scale and the Reasons of Student Dropout from Technical University - A. F. Smyk; V. I. Prusova; L. L. Zimanov; A. A. Solntsev (Высшее образование в России)
The article addresses the problem of student dropout from technical university due to their academic failure. The modern technical universities face a decline in youth’s interest to technical and natural sciences and engineering specialties. In enrolling new students on these specialties the universities have to set lower standards and requirements for the admission. So, the students are less motivated, and the number of expelled students increases.The article presents the results of data analysis for the two leading areas of training at Moscow Automobile and Road State Technical University (MADI) – “Construction of unique buildings and structures” and “Land transport and technological means” carried out respectively at the Road-Building faculty (DSF) and the faculty of Automobile transport (ATF). The article adduces the total number of students in MADI, as well as the number of the enrolled students on the specified training directions, and the number of expelled students of all courses for the period from 1935 to 2018. The results in physics exams showed by undergraduate students were compared with the Unified State Exam scores in physics. There is a clear parallel between the Unified State Exam scores, an entrance testing and “residual knowledge” tests.The authors have also analyzed the results of an anonymous questioning among the same groups of students, which make it possible to understand their point of view on the problems of learning difficulties. The main reasons for student attrition are both the low scores of the applicants’ results of the Unified State Exam, and insufficient actions and ineffective strategies undertaken by the university to involve undergraduate students in its educational environment.